Studi Penggunaan Obat Golongan Beta-Blocker Pada Pasien Rawat Inap Rumah Sakit Ansari Saleh Banjarmasin - Sari, Okta Muthia (Jurnal Farmasi Udayana; Vol. 9, No. 2, Tahun 2020, 2020)
Beta-blockers have a role in cardiovascular and non-cardiovascular therapy. Many beta-blockers are now available and in general they are all equally effective. There are, however, differences between them, which may affect choice in treating particular diseases or individual patients. Research related to the profile of beta-blocker drug use in cardiovascular and non-cardiovascular therapy is still limited. This study aims to describe the use of beta-blockers in inpatients at Ansari Saleh Hospital, Banjarmasin. This retrospective descriptive study was conducted from April to May 2019 at the Anshari Saleh Hospital, Banjarmasin. The beta-blocker drugs used were bisoprolol and propranolol which were administered in cardiovascular medications such as angina (3.7%); arrhythmia (3%); Congestive Heart Failure (20%); hypertension (3%); myocardial infarction (54.8%); non hemorrhagic stroke (9.6%); and non-cardiovascular including hepatic cirrhosis (1.5%); hyperthyroidism (4.4%). The bisoprolol dosage used by inpatients at Ansari Saleh Hospital starts from 1.25 to 5 mg per day. Myocardial infarction and non-hemorrhagic stroke patients received bisoprolol dose uptitration. The propranolol dosage is 20-30 mg per day. In cardiovascular patients, bisoprolol is a drug that is often given to patients with comorbids than propranolol. Keywords : Beta-blockers, cardiovascular, non-cardiovascular, therapy